The Public Interest of Tegal in Stock Investment during the Covid-19 Pandemic - Asyifa Maulida; Iswatun Khasanah; Yonif Mayoma (FEB Universitas Sultan Ageng Tirtayasa, 2022)
The Covid-19 pandemic is an outbreak that affects sectors of the economy, including stock investments. The purpose of this study was to determine the public interest of Tegal City in stock investment during the Covid-19 pandemic and provide overview or education related to stock investment in the people of Tegal City thus public can understand the stock as a whole. Data collection techniques by conducting surveys, literature studies and in-depth interviews. The population in this study was the entire people of Tegal city. This study used cluster sampling with a total of 152 respondents. The data analysis method used was descriptive statistical analysis, validity test, reliability test, normality test and simple linear regression analysis. The educational scheme implemented was to apply conceptual learning associated with the context of experience to help public understand and outline viewpoints related to stock investment. The conclusion is that the public interest of the Tegal City had significant influenced on stock investment during the Covid-19 pandemic. Educational scheme was implemented by applying conceptual learning that is associated with experiential.